Hinged and sectional complete dentures for restricted mouth opening: A case report and review - Aditi Sharma; Pallak Arora; Sartaj Singh Wazir (Wolters Kluwer Medknow Publications, 2013)
Restricted mouth opening is a definite prosthodontic hindrance to carry out treatment successfully. Restricted mouth opening can be due to many reasons such as microstomia, oral submucous fibrosis, some genetic disorder, and as a result of some surgical treatment. In the past, various techniques for prosthetic rehabilitation of limited oral opening have been tried such as surgeries, use of dynamic opening devices, magnetic devices, and modification of denture design. Here we present; a simplified technique and simple design for fabrication of maxillary hinged and mandibular hinged and sectional complete denture for a patient with restricted mouth opening due to oral submucous fibrosis.